Rancang Bangun Aplikasi Model 3 Dimensi Sebagai Media Pengenalan Ruang Bagi Mahasiswa Baru Dengan Pendekatan Luther Sutopo (Studi Kasus : Stt-Pln) - Abdul Haris; Monica Sianturi (Sekolah Tinggi Teknik - PLN, 2016)
Modeling three-dimensional (3D modeling) as one of the development of information technology to produce three-dimensional objects (3D) in the virtual world (virtual). In the virtual world, all objects can be explored such as the original world, can run in all directions, looking in all directions, and explore all of the objects in the virtual world, just as real. Progress modeling 3Dimensi also evolved as one of the media conduit of information to know the layout of the room of a building. PLN Technical High School has a storied building with twelve floors. From each floor enabled to where lectures each department. Sometimes the students, especially new students feel difficulty in recognizing the layout of the room. Writing this approach consisting Sutopo Luther-stage concept, design, collection of materials, manufacture, and testing, while for the design of three-dimensional modeling applied using Google Sketchup and Unity. Through this writing applications that are expected to be made as a medium to deliver information to students / i especially new students in the form of the introduction of the model space and layout of the existing space in 3D.